2016
DOI: 10.17583/qre.2015.1393
|View full text |Cite
|
Sign up to set email alerts
|

Genres of Underemployment: A Dialogical Analysis of College Graduate Underemployment

Abstract: With more individuals obtaining undergraduate and graduate degrees and the job market still recovering from the 2008 recession, the instances of college graduate underemployment (CGU) have increased throughout the United States.  College graduate underemployment is an employment condition that is characterized by subjective and objective factors, most prominent of which is an incongruence between one’s education and one’s current job. The intriguing nature of CGU is how both employment and education merge toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
0
5
0
1
Order By: Relevance
“…College graduates do not necessarily achieve middle‐class or higher social class status using their college degrees; they sometimes experience unemployment or underemployment mostly due to their underprivileged backgrounds (Cunningham, ; Scurry & Blenkinsopp, ). However, student affairs professionals may selectively reinforce students’ previously held beliefs that everyone on campus is given equal opportunity to succeed (Abowitz, ; Bowen et al, ), which is often called “The American Dream.” The way students make sense of “The American Dream” may vary individually, yet it is common that they strive and compete for however they define their “American Dream” (Terkel, ).…”
Section: Neglected Identities By Common Social Class Mythsmentioning
confidence: 99%
“…College graduates do not necessarily achieve middle‐class or higher social class status using their college degrees; they sometimes experience unemployment or underemployment mostly due to their underprivileged backgrounds (Cunningham, ; Scurry & Blenkinsopp, ). However, student affairs professionals may selectively reinforce students’ previously held beliefs that everyone on campus is given equal opportunity to succeed (Abowitz, ; Bowen et al, ), which is often called “The American Dream.” The way students make sense of “The American Dream” may vary individually, yet it is common that they strive and compete for however they define their “American Dream” (Terkel, ).…”
Section: Neglected Identities By Common Social Class Mythsmentioning
confidence: 99%
“…Distinguishing between the two, it was identified that unemployment is an all-or-nothing condition whereas underemployment has an array of objective and subjective factors that are crucial in defining it [19]. The objective factors of underemployment include number of hours worked, a worker's salary and a match between employee's expertise and his or her job [20], while subjective factors include perception of employees that they are overqualified for their present job and urge to use their work expertise remains unfulfilled [21].…”
Section: Underemploymentmentioning
confidence: 99%
“…In the case of higher education, value is obtained not through the venue of a given offering, but also through the receiver's perception of the offering which leads to expectations of the value of a given thing. Many times, students come into a university setting with the expectation that “obtaining a college degree is a sound gateway to gainful employment” in their area of interest (Cunningham, 2016, p. 3). Cunningham's (2016) study uncovered, “this expectation motivates the majority of the 1.8 million students in the United States who will earn a bachelor's degree” (p. 3).…”
Section: Perception and Valuementioning
confidence: 99%
“…Many times, students come into a university setting with the expectation that “obtaining a college degree is a sound gateway to gainful employment” in their area of interest (Cunningham, 2016, p. 3). Cunningham's (2016) study uncovered, “this expectation motivates the majority of the 1.8 million students in the United States who will earn a bachelor's degree” (p. 3). Also, those graduates anticipate starting salaries making much higher salaries than research shows are the reality.…”
Section: Perception and Valuementioning
confidence: 99%